Pengembangan Modul Permainan Tradisional untuk Memperkuat Hati Nurani Anak Usia 6-8 Tahun - Angela Reza Widi Pratiwi; Gregorius Ari Nugrahanta; Irine Kurniastuti (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2021)
This study aimed to develop a traditional game module on reinforcing the conscience of children aged 6-8 years. This research used research and development (R D) methods. The needs analysis involved five teachers from various regions, product validation involved three validators, and six children were involved in limited module trials. The results showed that 1) the traditional game module was developed based on ADDIE steps (Analyze, Design, Develop, Implement, and Evaluate). 2) The quality of the traditional game module had a mean score of 3.77 (scale 1-4), classified as